Green Extraction Combined with Chemometric Approach: Profiling Phytochemicals and Antioxidant Properties of Ten Species of the Lamiaceae Family - Branislava Teofilović; Emilia Gligorić; Martina Ninić; Saša Vukmirović; Žarko Gagić; Nebojša Mandić-Kovačević; Biljana Tubić; Đorđe Đukanović; Nevena Grujić-Letić (Separations, 2025)
The pharmacological potential of Lamiaceae plants is primarily linked to their high content of phenolic acids and flavonoids, known for strong antioxidant properties. This study investigated the antioxidant activity of ten widely used Lamiaceae herbs—oregano, lavender, basil, savory, garden thyme, wild thyme, sage, rosemary, lemon balm, and mint—prepared as traditional infusions and microwave-assisted extracts. The antioxidant capacity was evaluated using spectrophotometric assays, and total phenolics and flavonoids were quantified via spectrophotometry and HPLC. Chemometric analysis (PCA) was applied to explore correlations among antioxidant parameters. The results demonstrated excellent antioxidant activity across all samples. The IC50 for DPPH radicals was in the range from 3.73(0.13) to 8.03(0.17) μg/mL and that for ABTS radicals was from 2.89(0.12) to 8.55(0.34). The CUPRAC antioxidant assay delivered values in the range from 351.93(11.85) to 1129.68(44.46) μg TE/mg DE. The FRAP method produced values from 1.27(0.03) to 6.60(0.26) μmol Fe/mg DE. The presence of gallic acid was detected in all examined samples, with lemon balm and lavender exhibiting the highest concentrations across both applied extraction methods. Notably, lavender showed especially high levels of p-hydroxybenzoic acid and chlorogenic acid. Microwave-assisted extraction generally yielded higher levels of bioactive compounds compared to infusion. These findings highlight the potential of Lamiaceae herbal extracts, particularly those obtained through microwave-assisted extraction, as valuable sources of dietary antioxidants for everyday use.